Estudos de recuperação paralela na proposta curricular do estado de São Paulo (gestão 2007-2010) - Elliott, Edenilce Hortencia Jorge (2009)
This paper aims to critically analyze the parallel recuperation and remedial work projects and strengthening inserted in Curriculum Project Proposal São Paulo faz Escola, the Department of Education of the State of São Paulo (management 2007-2010), evaluating the actions as complicating or facilitating the construction of a curriculum that considers the pleasure of learning from students who, despite having completed at least six years of schooling in elementary school, have difficulty reading and writing. The analysis of the thematic investigation was based on theoretical lines of Apple(2006) and Gimeno Sacristán (1999, 2000) with respect to the ideological dimension of the curriculum. It was considered also the ideas of Lefèvre and Lefèvre (2002; 2003; 2005) for the construction of the discourse of collective subject. The study consisted of a qualitative analysis from literature, documentary and field. It was a survey of legislation on remedial work studies parallel the period covering the Laws 4024/61, 5692/71 and 9394/96, and the resulting legal devices. The field research used the interview as a tool for gathering information that led to the discourse of collective subject, representative voice of the students interviewed. This speech sought to register the meanings of parallel recuperation projects and capacity in relation to the pleasure of learning, as perceived and assigned by the students of two public schools in the state, located in the North zone of Osasco. There was a huge disparity between what has been proposed by the public policy of the State of São Paulo in relation to recovery projects and parallel strengthening and the needs of students